Cautionary Tales: Ethics and Case Studies in Science - Clyde Freeman Herreid (American Society for Microbiology, 2014)
Ethical concerns are normally avoided in science classrooms in spite of the fact that many of our discoveries impinge directly on personal and societal values. We should not leave the ethical problems for another day, but deal with them using realistic case studies that challenge students at their ethical core. In this article we illustrate how case studies can be used to teach STEM students principles of ethics.